Pemberdayaan Jama’ah Yasin Putri Sebagai Komunitas Belajar Untuk Pemantapan Gerak Dan Bacaan Shalat Fardhu di Desa Wagir Lor - Dyah Elisa Rosanti; Khoirul Fathoni (Social Science Academic, 2025)
This community service initiative aimed to empower the Yasin Putri Congregation in Wagir Lor Village through the Asset-Based Community Development (ABCD) approach to establish a self-sustaining learning community for improving the movements and recitations of obligatory prayers. The methodology encompassed five ABCD stages: formation of a core team, asset identification, potential mapping, resource linkage, and participatory monitoring. The results demonstrated a significant enhancement in prayer proficiency, the establishment of a peer-tutoring mechanism, and the creation of sustainable learning through optimizing local assets such as the mosque, guidebooks, and the congregation's internal capacities. This program confirms the effectiveness of an asset-based approach in fostering sustainable change and can serve as a replicable model for strengthening religious practices in other Muslim communities.